Improving a method for determining the spatial parameters in the mathematical model of a distributed automated information-measuring system for real-time control over the quality of iron ore raw materials - Azaryan, Albert; Shvets, Dmitriy; Hrytsenko Andrіі; Trachuk, Annait; Cherkasov, Oleksii; Shvydky, Oleksandr (Eastern-European Journal of Enterprise Technologies, 2025)
This study investigates processes of irradiating iron ore raw materials by a source of low-energy gamma quanta and registering radiation scattered as a result of the Compton effect, as well as parameters of the irradiation geometry. This work addressed the task of improving the accuracy of existing nuclear-physical methods of control over the quality of iron ore raw materials, which make it possible to promptly determine the material composition of the crushed rock mass. The results essentially indicate that when using a centrally shifted irradiation geometry, the sensitivity of registration of the integral backscatter flux increases compared to the side and central irradiation geometries. This is attributed to improved visibility conditions of the detector, and the formation of a scattering angle close to the optimal. The constructed mathematical model has made it possible to identify the main geometric parameters for the system of operational control over the quality of iron ore raw materials. A formula has been derived that connects the basic parameters in the system of operational control over iron content in ore with the use of centrally shifted irradiation geometry. The studies demonstrated changes in the sensitivity of the registration of the integral backscatter flux when changing the vertical location of the gamma-ray source. The results revealed a maximum sensitivity with a value of 6.08·10-7 at a minimum distance of the radiation source from the single crystal and a distance of 110 mm from the irradiated surface. The value of the correlation coefficient between the model and experimental data is 0.981. The findings could be practically applied to improve the accuracy of methods for operational control over the content of a usable component in iron-containing ores under industrial conditions at ferrous metallurgy enterprises